ANALISIS SEMIOTIKA MAKNA BERBAGI PADA VIDEO LAZISMU BERJUDUL SARUNG BERLUBANG - Cholifah Nurhasanah (STID Al-Hadid, 2021)
This study aims to determine the meaning of sharing contained in Lazismu’s video titled “Sarung Berlubang” by analyzing verbal and nonverbal signs available. Lazismu delivered a da’wah message in the form of an invitation of sharing by displaying few verbal messages but more messages in the form of sogns with hidden meanings. It makes mad’uw not feel forced to share and can build awareness because of its implicit but persuasive content. This qualitative study uses Ferdinand de Saussure’s semiotic analysis approach. In data analysis, it uses Ferdinand de Saussure’s semiotic elements to assess signs available in the video, namely: (1) Signs; (2) Signifier; (3) Signified. The connection between those elements is analyzed to be certain meanings called signification. It indicates that a message in the form of social values on sharing is displayed on the video, in both visual and audiovisual perspectives. Through this video, people are not only invited to share with others, but also are given a description on the meaning of sharing.